2008
DOI: 10.1080/14622200701767829
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cigarette smoking and the microstructural integrity of white matter in healthy adults: A diffusion tensor imaging study

Abstract: Results from recent studies suggest that chronic cigarette smoking is associated with increased white matter volume in the brain as determined by in vivo neuroimaging. We used diffusion tensor imaging to examine the microstructural integrity of the white matter in 10 chronic smokers and 10 nonsmokers. All individuals were healthy, without histories of medical or psychiatric illness. Fractional anisotropy (FA) and trace were measured in the genu, body, and splenium of the corpus callosum. FA provides a measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
94
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 43 publications
12
94
1
2
Order By: Relevance
“…The nicotine-induced cytotoxic swelling suggested by Gazdzinski et al (22) and proinflammatory effects of cigarette smoke on tissue as shown by elevated peripheral leukocytes, and recruitment of polymorphonuclear cells, monocytes, macrophages, and increased fibrinogen may be partly responsible for cellular edema and reduced MD levels in the H S of the current study (23). Some recent studies have hypothesized on the neurotropic and promyelinating effects of smoking and have found higher FA in brain regions such as the prefrontal WM, cingulum, and corpus callosum in smokers compared with nonsmokers (9,24). Yet, another study on heavy smokers reported decreased FA in the anterior corpus callosum (25).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The nicotine-induced cytotoxic swelling suggested by Gazdzinski et al (22) and proinflammatory effects of cigarette smoke on tissue as shown by elevated peripheral leukocytes, and recruitment of polymorphonuclear cells, monocytes, macrophages, and increased fibrinogen may be partly responsible for cellular edema and reduced MD levels in the H S of the current study (23). Some recent studies have hypothesized on the neurotropic and promyelinating effects of smoking and have found higher FA in brain regions such as the prefrontal WM, cingulum, and corpus callosum in smokers compared with nonsmokers (9,24). Yet, another study on heavy smokers reported decreased FA in the anterior corpus callosum (25).…”
Section: Discussionmentioning
confidence: 85%
“…The variable degrees of addiction of smoking in the participants might be one important factor in these contradictory research findings. Although limited dependence and exposure to nicotine revealed no significant change, heavy smoking exposure showed marked FA reductions in WM (9,24). Whether FA or MD is more sensitive and an earlier measure of WM disintegrity remains controversial in the literature (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2011) revealed a reduction in the microstructural integrity of the cerebral WM in cigarette smokers. Changes in DTI findings related to smoking behavior have been demonstrated in multiple regions, including the corpus callosum, internal capsule, and prefrontal WM at multiple levels (Hudkins, O'Neill, Tobias, Bartzokis, & London, 2012; Paul et al., 2008; Zhang, Stein, & Hong, 2010). In our study, after controlling for the number of pack years of smoking, there was no observable group difference in the ADC in the posterior corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine has been held responsible for the majority of the detrimental effects of smoking on the CNS [6][7][8]. It acts as an agonist within the cholinergic neurotransmitter system and nicotinic receptors are widely distributed within the CNS with the highest density in the thalami [6,9,10].…”
Section: Introductionmentioning
confidence: 99%